Estimation of the atmospheric greenhouse gas spatial distribution in the Arctic using a back trajectory model. (12th November 2019) - Poddubny, Vassily; Nagovitsyna, Ekaterina; Antonov, Konstantin; Markelov, Jury; Buevich, Alexander; Omelkova, Elena; Manzhurov, Igor; Medvedev, Alexander; Vasilyeva, Julia
Abstract : We present a method and results of the retrieval of average effective fields of atmospheric impurity concentration using a passive wind sensing (remote sensing) numeric technology referred to as Fluid Location of the Atmosphere (FLA). The quasi‐two‐dimensional problem of reconstruction of the spatial distribution of the greenhouse gases assuming the diffusion Peclet number infinitely large was solved numerically. The study is based on in‐situ measurements of the atmospheric methane and carbon dioxide during the expeditions to Belyy Island in the Kara Sea in July and August of 2016 to 2017. The differences and common features of CH4 and CO2 spatial distribution in this region of the Arctic during specified periods were analyzed. CH4 concentrations tended to decrease with moving from the continent to the remote sea areas. For CO2 on the contrary, lower values were observed over the continent, and they increased with a distance from the coastline. For both greenhouse gases, average atmospheric concentrations increased in 2017 relative to 2016.